Defasagem do IPTU no município do Rio de Janeiro: Uma proposta de reforma - Pedro Humberto Bruno de Carvalho Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper seeks to analyze the tax revenue level and the equity of the Brazilian real estate tax (IPTU) in the city of Rio de Janeiro, showing the main factors for its performance. The first two chapters confirm, based on theory, the necessity of progressiveness in the IPTU taxation system, and the legal and economic points of view, respectively. These chapters also show the extra fiscal characteristics of IPTU, because it impacts the price of urban land, it causes the best use of land and it can be used as an instrument of urban policy. The indicator for the property tax collection in Brazil is at a lower level compared to the developed countries and some developing countries and there is a high heterogeneity among Brazilian cities, with the concentration of revenues in the Midwest, Southeast and South Regions and in the major cities. In your administration, the IPTU needs a real estate appraisal system to measure the value of property that will be taxed. The system is efficient when there is not a high gap in relation to market values when there exists appraisal homogeneity among properties of similar market value (horizontal equity) and there does not exist a lower gap appraisal between the properties more highly valued (regressivity). Based on a sample of 8,408 apartments appraised by CAIXA Bank between 2006 and 2009, the values appraised by this bank were compared by officials values as well as the amount taxed by the IPTU on each unit. Came to the conclusion that the officials values were at a level that represented between 26.7% to 38.5% of the values assessed by the bank. The study found high horizontal inequity, where in some areas of the city, the official values were most outdated than others. Additionally, the factor of depreciation for age, technical index that exists in the tax law of Rio de Janeiro, depreciates all the value of the properties according to its age (up to 50%), conjunction with the reductions and discounts given by the legislature, were responsible for depleting the officials values in 45% in the sample of apartments. This impacted greatly the collection and did become the vast majority of the properties in the sample exempts of IPTU. Despite the high gap between assessments, analyzing the distribution of the official values appraised, it was found that there was just a small regressivity in the assessments. Moreover, when analyzing the IPTU taxation, we see that it taxes more heavily the most valued properties, thus having progressive distribution, because the tax reduction criteria benefited the properties with lower value. Thus, the study concluded that there is necessary a IPTU tax reform Rio de Janeiro, updating the official values and revising the correction factors and the political criteria for tax reduction. Especially the paper proposes that the factor of depreciation for age depreciate up to 34% the properties in the quarters from the South Zone and up to 42% the properties from other quarters, because the first region has a higher land value composition in the all property value.
Keywords: H23; H24; H71; R52; 330; public sector economics; property taxation; tax progressivity; real estate appraisal; fiscal federalism; Grunderwerbsteuer; Rio de Janeiro